Studying the relationship of agility and reaction speed with some offensive skills in basketball (Journal of the College of Basic Education, 2022)
As a result of the evolution in the science of knowledge all in the sports field, in particular it is necessary to follow the scientific formulas effective to find the strengths and weaknesses in performance and to identify the relationship of some physical attributes level of performance skills of the game of basketball being one of the gaming public, which received wide spread in recent and the fact that strands of elegance and speed of reaction and found effective in that game it is necessary to know the extent of the relationship between these qualities and the level of performance of some offensive skills in the game of basketball, my goal was the research are: -1 - To determine the relationship between status and level of fitness to perform some offensive skills basketball.2 - To determine the relationship between the status of the speed of reaction and the performance of some of the skills of offensive basketball. The hypothetical research were two: -1 - There is a correlation between the status and level of fitness to perform some offensive skills basketball2 - There is a correlation between the status of the speed of reaction and the performance of some of the skills of offensive basketball, also included research on the applied fields, which are human, spatial and temporal, this was a summary of what came in the door first, and also includes research also clarify appropriate in Part II for threads theory, which shows an explanation of the concepts of agility and speed of reaction and Astkhaddamathma in the game of basketball, and move to Part III we find includes the most important procedures and field test reconnaissance and main carried out by the researcher also included research presentation of results in Section IV, and after analysis and discussion has been reached in Part V to a group of the conclusions of which1 - There is a correlation between moral character and fitness level of the performance of some offensive skills basketball2 - and a significant correlation between the row of reaction speed and the level of performance of some offensive skills basketball, but the most important recommendations were1 - emphasis on the development of the fitness status of their wealth is a clear technical and performance skills of the game of basketball.2 - The need attention and focus on the training status of the speed of reaction to being an effective role in capacity offensive skill to resolve the outcome of the game